Efficacy of conservative treatment of perianal abscesses in children and predictors for therapeutic failure - Lars Boenicke; Johannes Doerner; Stefan Wirth; Hubert Zirngibl; Mike Ralf Langenbach (The Korean Pediatric Society, 2020)
Background The optimal management of perianal abscess in children is controversial. Purpose To evaluate the efficiency of conservative treatment of perianal abscess in children and identify parameters that predict therapy failure. Methods All cases of children younger than 14 years of age with perianal abscesses between 2001-2016 were evaluated. Results Of the 113 enrolled patients, 64 underwent subsequent surgery for advanced disease (primary surgery group). Conservative treatment was initiated in 49 patients (primary conservative group) but was stopped because of inefficiency in 25 patients, who were referred for surgery after a median 7.03 days (range, 2 to 16 days). The other 24 patients (48%) initially achieved complete remission after conservative treatment, but 10 were readmitted after a median 34 months (range, 3 to 145 months) with recurrent disease. There were no significant differences in permanent success after conservative treatment between infants (10 of 29, 34%) and older children (4 of 20 [20%], P=0.122). Overall, conservative treatment alone was effective in only 14 of 113 patients. Recurrence after surgery occurred in 16 patients (25%) in the primary surgery group and 11 patients (22%) in the primary conservative group (P=0.75). Univariate analysis of predictors for conservative treatment failure revealed inflammatory values (C-reactive protein and white blood count, P=0.017) and abscess size (P=0.001) as significant parameters, whereas multivariate analysis demonstrated that only abscess size (odds ratio, 3.37; P=0.023) was significant. Conclusion Conservative treatment of perianal abscess is permanently efficient in only a minority of children but is not associated with a higher recurrence rate after subsequent surgery. Abscess size is a predictor for therapy failure.